2021
DOI: 10.3390/su13052972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on Growth, Physiology of Plants, Yield and Grain Quality of Different Spring Wheat (Triticum aestivum L.) Genotypes

Abstract: Heat stress is one of the major threats to wheat production in many wheat-growing areas of the world as it causes severe yield loss at the reproductive stage. In the current study, 28 crosses were developed using 11 parental lines, including 7 female lines and 4 male testers following line × tester matting design in 2018–2019. Twenty-eight crosses along with their 11 parental lines were sown in a randomized complete block design in triplicate under optimal and heat stress conditions. Fifteen different morpho-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…However, the created inter-and intraspecific variation conditions genetic analysis and selection processes [5]. Analysis of variance showed significant variation among genotypes and their combinations [35]. In this context, our results exposed that there was considerable variation among the parental genotypes for different traits in experiments were conducted.…”
Section: Discussionmentioning
confidence: 57%
“…However, the created inter-and intraspecific variation conditions genetic analysis and selection processes [5]. Analysis of variance showed significant variation among genotypes and their combinations [35]. In this context, our results exposed that there was considerable variation among the parental genotypes for different traits in experiments were conducted.…”
Section: Discussionmentioning
confidence: 57%
“…It was also founded that 1°C increase in temperature could reduce grain yield by 6%. (Riaz et al, 2021) reported that wheat grain yield is highly influenced by photosynthesis, which is one of the most important physiological processes for the plant.…”
Section: Effect Of Sowing Datesmentioning
confidence: 99%
“…Considerable genetic variation was observed between wheat genotypes for their resilience to high temperatures. To improve or develop wheat genotypes for high temperatures tolerance, the initial step is to assess all the cultivated species genetic variability for high temperatures tolerance and to select genotypes a high ability to withstand heat stress (Riaz et al, 2021).…”
Section: Mean Performance Of Genotypesmentioning
confidence: 99%
“…Wheat is one of the three major crops in the world and the leading food crop in China, and its yield plays a key role in the food security and socioeconomic development of China (Slafer, 2003). High temperature in the post-anthesis period often accelerates wheat maturation and, thus, severely reduces wheat yield and quality (Riaz et al, 2021). Grain number is mainly determined during the period immediately preceding anthesis, and individual grain weight is defined during the grain-filling period (Karim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%